Overview of Indonesia's Role in the South China Sea Conflict - Renaldi Renaldi; Fricean Tutuarima; Fatimah Sialana (CV. Rayyan Dwi Bharata, 2023)
This Study aims to determine the process of resolving the south China Sea conflict by the Indonesian government, which until now has not been resolved due to overlapping claims between China, Vietnam, the Philippines, Brunei Darussalam and Taiwan. The South China Sea conflict is heating up, causing concern and threats in the Asian region. Because the South China Sea is an international route, where the South China Sea is used a shortcut by countries in the world. Because the South China Sea is used as a shortcuts Asia, Europe and the South China Sea has a very important position for the world economy. If there is a conflict in the South China Sea it will greatly hamper the world economy. The data collection technique for this research is library research, in which the data is obtained from secondary data such as books, journals, news and so on that are related to the research being studied. This research refers more to the resolution of the South China Sea conflict by the Indonesian government.